ERGONOMIC ASPECTS OF TEACHING - Elena S. Yatsenko; Irina K. Tinina (Высшее образование в России)
The empirical basis of article is the results of study of production factors and ergonomic environment at the Chemistry Department of Altai State University. The data obtained can be used for workplace organization for teachers, helping to prevent the occurrence of professional diseases, and improve the effectiveness of educational and professional activities.